Quantum Nano-Photonics (NATO Science for Peace and Security Series B: Physics and Biophysics,, 2018)
This book brings together more closely researchers working in the two fields of quantum optics and nano-optics and provides a general overview of the main topics of interest in applied and fundamental research. The contributions cover, for example, single-photon emitters and emitters of entangled photon pairs based on epitaxially grown semiconductor quantum dots, nitrogen vacancy centers in diamond as single-photon emitters, coupled quantum bits based on trapped ions, integrated waveguide superconducting nanowire single-photon detectors, quantum nano-plasmonics, nanosensing, quantum aspects of biophotonics and quantum metamaterials. The articles span the bridge from pedagogical introductions on the fundamental principles to the current state-of-the-art, and are authored by pioneers and leaders in the field. Numerical simulations are presented as a powerful tool to gain insight into the physical behavior of nanophotonic systems and provide a critical complement to experimental investigations and design of devices.